Best practices for interdisciplinary care of uncontrolled severe asthma patients (TEAM project) - Mónica Climente-Martí; Pilar Ausín-Herrero; Nuria Carballo-Martínez; Vicente Merino-Bohórquez; Ana Gómez-Bastero; Víctor Manuel López-García (Farmacia Hospitalaria)
As one of the most prevalent chronic respiratory diseases, asthma imposes a heavy health and socioeconomic burden on society, particularly in the case of patients who fail to appropriately control the disease. For this reason, improving the clinical management of patients with severe uncontrolled asthma should be a priority for any healthcare system. At a time when healthcare models for chronic disease management and personalized medicine are undergoing a major overhaul, the project presented in this study seeks to lay the foundations for an interdisciplinary care model for patients with severe uncontrolled asthma. The work carried out reinforces the general perception that it is paramount to optimize coordination between different levels of care, encourage collaboration and an interdisciplinary approach, and promote an integrated care model that makes it possible to adapt the care of patients with severe uncontrolled asthma in a more personalized manner. Under this project, a series of interdisciplinary working groups were created, made up of specialist hospital pharmacists, pneumologists and allergists, to identify and prioritize a number of best practices, and classify them in terms of their potential impact on the improvement of the quality of care and the health outcomes of patients with severe uncontrolled asthma, and their feasibility. The authors’ ambition is that the conclusions drawn from this study should help other interdisciplinary teams improve the care provided to patients suffering from